ISLAMIC FINANCE AND COSO ERM: EXAMINING STRATEGIC DRIVERS OF PERFORMANCE IN SHARIA BANKS - Zuraidah, Zuraidah; Wahidmurni, Wahidmurni; Diana, Ilfi Nur (EL DINAR: Jurnal Keuangan dan Perbankan Syariah, 2024)
This study investigates the impact of Enterprise Risk Management (ERM) disclosure, guided by the Committee of Sponsoring Organizations (COSO) framework, on the financial performance of Islamic banks. It further examines the mediating roles of Critical Success Factors (CSF) and Islamic Corporate Governance (ICG). Utilizing secondary data from financial reports spanning 2014 to 2023, the sample comprises the world’s ten largest Islamic banks as ranked by Global Finance in 2022. Path analysis with Feasible Generalized Least Squares (FGLS) estimation was employed. The findings reveal that COSO ERM disclosure has a significant direct negative effect on financial performance. Interestingly, COSO ERM significantly influences both CSF and ICG, and ICG, in turn, significantly impacts financial performance. However, CSF do not demonstrate a significant direct effect on financial performance. Furthermore, neither CSF nor ICG significantly mediates the relationship between COSO ERM and financial performance. These results suggest that while COSO ERM enhances internal strategic and governance mechanisms, its influence on financial outcomes may necessitate more profound integration. This research contributes to risk management literature by incorporating the COSO ERM framework within the context of Islamic banking.